Effect of dry fermented feed with probiotic on the production performance of Akar Putra chicken - Idris, Lokman Hakim; Jawad, Hasan S. A.; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
During recent years solid state fermented feed (SSFF) has been introduced with great success in poultry nutrition, it shown some beneficial properties, in particular, considering animal health. The present experiment was conducted to evaluate the effect of dry fermented feed with prepared probiotic (PP) on the live body weight, weight gain, feed intake and feed conversion ratio of a local Malaysian chicken (Akar Putra). The experiment comprised 3 treatments (24 chicken/ treatment), with 3 replicates for each (8 chicken/ replicate). Experimental treatments consist of a control treatment T1, the mixture of SSFF and PP were used in T2 and T3 treatments. (SSFF+ PP) Mixture in the second treatment was prepared at the rate 1:1:1 (1 kg of commercial broiler feed+ 1 liter tap water+ 1 gram PP). While the rate was 1:1:2 (1 kg of commercial broiler feed+1 liter tap water+ 2 gram PP) in T3 treatment. These mixtures were placed in a plastic tray, incubate for 38 h. at 37±2 ºC for complete fermentation and used after drying. The results revealed remarkable significant (P<0.01) enhancing for supplementing treatments than the control group in all of males' and females' body weight, weight gain, feed intake and feed conversion ratio measurements. Variation ratio of production performance parameters for supplementing treatments than the control group was calculated to support the results. Best results were indicated in T2 treatment when the chickens fed on dry feed mixture with 1gram prepared probiotic.